Stem aquaporins and surfactant-related genes are differentially expressed in two Eucalyptus species in response to water stress - Feltrim, Daniela; Pereira, Luciano; Costa, Marília Gabriela de Santana [UNESP]; Balbuena, Tiago Santana [UNESP]; Mazzafera, Paulo (Elsevier, 2021)
The regulation of water column tension in the xylem is essential to avoid embolism formation. Plants can actively reduce the hydraulic resistance in the xylem by moving water from the neighbourhood living cell, via aquaporins. They can also produce substances known as surfactants which stabilise nanobubbles avoiding embolism. Transcriptomic and proteomic data were used to test the presence of these two mechanisms in stems of Eucalyptus grandis and E. globulus grown at two temperature treatments (10–12°C and 33–35°C), thus at different vapour-pressure deficit (VPD) conditions. In both temperatures, plants were kept well-watered. Ten aquaporin genes (6 PIPs and 4 TIPs) and seven surfactant related genes (two phospholipid/glycerol acyltransferase and five lipid-transfer protein – LTP) were identified. Six aquaporins and two surfactant-related proteins identified in the proteomic analysis matched the transcriptome data. Seven aquaporin genes were up-regulated under 30°C, and high VPD in E. globulus (PIP1;2, PIP2;7, PIP1;4, TIP2;1, TIP1;3, TIP1;3(2), and TIP2;1(2)) and three were down-regulated (PIP2;5, PIP2;2, and PIP2;6). We also stressed plants of both species and analysed aquaporin and surfactant-related gene expression along with water stress development. The results showed that they also respond to water stress. Although we could not isolate the effect of temperature in the proteome and transcriptome experiments, our results suggest that aquaporins and surfactants can be involved in the reduction of embolism in eucalyptus under high xylem tension, by allowing radial transport of water in the stem and stabilising nanobubbles, respectively.
Keywords: Capacitance; Cavitation; Conductance; Embolism; Hydraulic; Radial hydraulic